2018
DOI: 10.1038/s41598-018-24348-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic use for acute bronchiolitis on new-onset asthma in children

Abstract: Early-life use of antibiotics is associated with asthma. We examined the effect of antibiotic use for early-life bronchiolitis on the development of new-onset asthma in children from Taiwan between 2005 and 2010. Data were from the National Health Insurance Research Database 2010, and diseases were coded using the International Classification of Disease (ICD). We classified the patients, all of whom had bronchiolitis, as having asthma or not having asthma. Asthma was diagnosed using ICD criteria and by use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…However, the long-term use of antibiotics results in the emergence of drug-resistant strains [12]. At the same time, an increasing number of studies have shown that children and pregnant women exposed to antibiotics are at increased risk of asthma later in life or in their newborn babies, and this risk is positively correlated with an increased antimicrobial spectrum and an increased antibiotic dosage [69][70][71][72]. The GINA report does not support the use of antibiotics for asthma, and it is recommended that antibiotics should not be routinely used to treat exacerbations of asthma unless there is definitive evidence of pulmonary infection (e.g., radiological evidence of pneumonia, fever or suppurative sputum) [2].…”
Section: Use Of Antibioticsmentioning
confidence: 99%
“…However, the long-term use of antibiotics results in the emergence of drug-resistant strains [12]. At the same time, an increasing number of studies have shown that children and pregnant women exposed to antibiotics are at increased risk of asthma later in life or in their newborn babies, and this risk is positively correlated with an increased antimicrobial spectrum and an increased antibiotic dosage [69][70][71][72]. The GINA report does not support the use of antibiotics for asthma, and it is recommended that antibiotics should not be routinely used to treat exacerbations of asthma unless there is definitive evidence of pulmonary infection (e.g., radiological evidence of pneumonia, fever or suppurative sputum) [2].…”
Section: Use Of Antibioticsmentioning
confidence: 99%
“…[7][8][9] There is also evidence that identifying RSV in infants who were affected was independently associated with discontinuation of antibiotics during hospitalization; however, it is unclear whether the issuance of guidelines can affect the use of antibiotics. [10][11][12] Our primary study aim was to examine antibiotic prescribing practices as part of the inpatient management of bronchiolitis at a single tertiary care pediatric hospital before and after the publication of the CPS guidelines in November 2014. Given concerns about the overuse of antibiotics as a major contributor to antibiotic resistance, we wanted to determine if the release of national guidelines was associated with a reduction in antibiotic use for this illness.…”
mentioning
confidence: 99%
“…Our previous study also concluded that, in children, 5 preceding years of antibiotic exposure, predominantly to amoxicillin and macrolides, was associated with the risk of asthma development in AR and in bronchiolitis 17 , 18 . However, the risk of the development of new-onset asthma in AD patients due to early-life antibiotic exposure is still unknown.…”
Section: Introductionmentioning
confidence: 66%